PENINGKATAN KAPASITAS MASYARAKAT DESA RINDU HATI DALAM PENGEMASAN PRODUK UNGGULAN - Yessilia Osira; Evanila Sivia; Septri Widiono (Universitas Bengkulu, 2020)
Community capacity building is an effort to increase the ability, skills, understanding, attitudes, values, relationships, behavior, motivation, resources, and conditions that enable each individual, organization, network and wider system to carry out functions them and achieve the stated development goals from time to time. Based on this understanding, Bengkulu University through community service activities made efforts to increase the capacity of residents of Rindu Hati Village in Processing Superior Products. The method used in the activity was the socialization of a Home Industry Product (PIRT) permit and the introduction and practice of packaging superior products in the form of processed papaya foods and processed red picking coffee. The results of this activity show that there is a growing awareness that packaging superior village products and PIRT management are requirements that the products produced can be widely marketed to the community.